Pengembangan E-LKPD Berbasis Inkuiri Terbimbing pada Materi Asam dan Basa untuk Kelas IX SMA/MA - Zakiya, Ratu; Kurniawati, Desy (Entalpi Pendidikan Kimia, 2024)
One of the innovations in developing teaching materials that utilize technology and learning approaches is to modify printed LKPD into electronic form which is prepared using a learning model. This research aims to develop a valid and practical guided inquiry-based E-LKPD on acid and base subject for class XI SMA/MA. The type of research used is design research with a plomp development model. The results of this research show that the E-LKPD developed is valid and practical. The average content validity value of E-LKPD is 0.85 with a valid category and the average construct validity value of E-LKPD is 0.85 with a valid category. The average value of practicality analysis is 92% for teacher practicality in the very practical category and 88% for students' practicality in the very practical category.